Ecological Index And Ecosystem Status Of Mangroves In The Waters Of Parang Island, Seram Bagian Timur Regency, Maluku Province - M. Taufiq; Masudin Sangaji; Niette V. Huliselan (International Journal of Science and Environment (IJSE), 2024)
The mangrove ecosystem on Parang Island is one of the important habitats in supporting the productivity of the surrounding waters. Therefore, an analysis of the condition of the mangroves on Parang Island is very important to understand the status and trend of changes in the mangrove ecosystem, so that appropriate conservation and management strategies can be formulated. This study aims to determine the physical-chemical parameters of the waters, analyze the density, percent cover, and status of the mangrove ecosystem in the waters of Parang Island. Mangrove data was collected using the belt transect method, while the physical and chemical parameters of the waters were measured in-situ by making observations at 4 research stations. The results showed that the average water temperature at each station ranged from 29.5°C, the average salinity was 26 ppt, the average current speed was 0.24 m/s, the average pH was 5.25, and the average clarity was 73.18%. There are 4 species of mangroves in the waters of Parang Island, namely Rhizophora apiculata, Rhizophora stylosa, Sonneratia alba, and Bruguiera gymnorhiza. The highest average relative density in the tree category is owned by Rhizophora apiculata, and the lowest is represented by Brugueira gymnorhiza. The highest sapling category is represented by Rhizophora stylosa, and the lowest by Brugueira gymnorhiza, while for the seedling category, the highest relative density is represented by Rhizophora apiculata, the lowest by Sonneratia alba. The highest average mangrove cover is owned by the Rhizophora apiculata species, and the lowest is represented by the Brugueira gymnorhiza species. The condition of the Rhizophora apiculata mangrove is in a moderate status, while Rhizophora stylosa, Sonneratia alba, and Brugueira gymnorhiza species are in a rare status.